Guideline-directed therapy at discharge in patients with heart failure and atrial fibrillation. Issue 4 (6th September 2019) - Ahn, Min-Soo; Yoo, Byung Su; Yoon, Junghan; Lee, Seung-Hwan; Kim, Jang Young; Ahn, Sung Gyun; Youn, Young Jin; Lee, Jun-Won; Son, Jung-Woo; Kim, Hye Sim; Kang, Dae Ryong; Cho, Hyun-Jai; et al.
Abstract : Objectives: This study evaluated the relationship between guideline adherence for recommended therapy on discharge and relevant 60-day and 1-year clinical outcomes in patients with acute heart failure (HF) with reduced ejection fraction and atrial fibrillation (AF). Methods: Of 5625 acute patients with HF in the Korean Acute Heart Failure registry, 986 patients with HF and documented AF were analysed. Guideline adherence scores were calculated for the prescription of ACE inhibitors, angiotensin receptor blockers, β-blockers, mineralocorticoid receptor antagonists and anticoagulants. Results: In patients with HF with AF, there was a significant trend of reduced 60-day and 1-year mortality rates and the composite end point with guideline adherence. According to the Cox proportion hazard model, poor adherence was associated with a significantly higher risk of 60-day mortality (HR 4.75; 95% CI 1.77 to 12.74) and the composite end point (HR 2.36; 95% CI 1.33 to 4.18) compared with good adherence. Furthermore, poor adherence was associated with a significantly higher risk of 1-year mortality compared with moderate (HR 1.64; 95% CI 1.15 to 2.33) and good adherence (HR 2.34; 95% CI 1.39 to 3.97) and with a higher risk of the 1-year composite end point compared with good adherence (HR 1.58; 95% CI 1.07 to 2.33). Conclusion: Better adherence to guidelines was associated with better 60-day and 1-year prognoses in patients with HF with AF.